Syntactic difficulties encountered by native speakers in learning a second language in sri lanka: based on concord of sentences - Srikantharajah, S. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
In Multilingual society, Native speakers tend to learn a Second Language which has become very popular in Sri Lanka after promoting the trilingual studies at Schools, Universities and professional sectors and it also one important way of fostering and perpetuating national unity in Sri Lanka. When the attention is focused on Learning Tamil or Sinhalese as a Second Language as a beginner in the first year at university of Jaffna and University of Kelaniya, it has been observed that the learners who don’t have any knowledge in Tamil or Sinhalese as a Second Language before the university entrance find it difficult to comprehend the concord of sentences which include animate and inanimate nouns as subjects and the verb ‘to be. Particularly due to the interference of First Language learners of Second Language find it difficult at the initial stage of learning the Language. Furthermore, when constructing sentences the learners have the tendency to translate literally following the syntactic rules of their first language. The study focuses on syntactic difficulties regarding the Subject Predicate agreement of sentences encountered by Native speakers of Tamil/Sinhalese Languages. Research sample of this study limited to 30 students at beginner level of university of Jaffna and University of Kelaniya. The data was collected by reviewing the questionnaire, analysing the students’ performance and classroom observation were also done in order to gather data. In conclusion this study helped to find out the errors regarding the concord of sentences done by students and it is believed that this kind of study would facilitate the teachers’ task of preparing teaching materials. Also it is recommended to teach Tamil while comparing the grammar rules with Sinhalese.
Keywords: Animate nouns; Concord; Inanimate nouns; Interference; First Language; Second Language